1999
DOI: 10.1038/16833
|View full text |Cite
|
Sign up to set email alerts
|

Yeast cell-type regulation of DNA repair

Abstract: cryptic a and Ȋ genes resident at the HML and HMR loci. As a result, sir mutant strains have the properties of a/Ȋ diploids.Non-homologous end-joining (NHEJ) is required in mammals both for V(D)J recombination 2 and for repairing doublestranded DNA breaks. NHEJ also occurs in yeast 3,4 , and it has been reported that Sir proteins are required for this process 5,6 . This observation was interpreted to mean that Sir proteins are involved directly in NHEJ, perhaps by forming a heterochromatin-like structure at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(33 citation statements)
references
References 1 publication
4
29
0
Order By: Relevance
“…In such cells, homology-driven repair is impossible and therefore NHEJ may be required. This is consistent with the findings that showed that NHEJ efficiency is increased in stationary [152] and haploid cells [153] (see sections below) compared to exponentially and diploid cells, respectively. Notably, the lig4 or lif1 mutant is not UV sensitive [40][41][42]44].…”
Section: Ligation Factors Of the S Cerevisiae Non-homologous End-joisupporting
confidence: 93%
“…In such cells, homology-driven repair is impossible and therefore NHEJ may be required. This is consistent with the findings that showed that NHEJ efficiency is increased in stationary [152] and haploid cells [153] (see sections below) compared to exponentially and diploid cells, respectively. Notably, the lig4 or lif1 mutant is not UV sensitive [40][41][42]44].…”
Section: Ligation Factors Of the S Cerevisiae Non-homologous End-joisupporting
confidence: 93%
“…The assay consists of transforming a linearized plasmid and counting the transformants that repaired the linear plasmid to convert it into a circular and thereby stably maintained plasmid (Åström et al 1999;Lee et al 1999). We found that esa1-414 and esa1Δ sds3Δ strains had increased NHEJ repair efficiency compared to wild type, one possible reason for their DNA damage sensitivity phenotypes ( Figure 5B).…”
mentioning
confidence: 80%
“…Assays with pRS316 were performed with established methods (Åström et al 1999;Lee et al 1999). Four independent experiments were performed, and P-values were calculated using the Student's t-test.…”
Section: Plasmid End-joining Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…A first indication that NHEJ is under active control in S. cerevisiae appeared in the late 1990s when it was demonstrated that this process is down-regulated by Mata1-Matα2, resulting in less efficient NHEJ in diploid cells compared to haploid cells [7,8]. Subsequently, the responsible target protein, Nej1, was identified [9][10][11][12] and shown to be encoded by a haploidspecific gene, expression of which is virtually undetectable in the presence of Mata1-Matα2 because of a consensus-binding site for this repressor in the NEJ1 promoter [9,10].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%